2022
DOI: 10.3390/rs14195024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Anthropogenic CO2 Bottom-Up Emission Inventories Using Satellite Observations from GOSAT and OCO-2

Abstract: Anthropogenic carbon dioxide (CO2) emissions from bottom-up inventories have high uncertainties due to the usage of proxy data in creating these inventories. To evaluate bottom-up inventories, satellite observations of atmospheric CO2 with continuously improved accuracies have shown great potential. In this study, we evaluate the consistency and uncertainty of four gridded CO2 emission inventories, including CHRED, PKU, ODIAC, and EDGAR that have been commonly used to study emissions in China, using GOSAT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We would extend the study areas, such as the American land area, to validate our proposed approach in the future. Another additional study built the grid-based prediction model by generalized regression neural network (GRNN) algorithm using a long time series of data from 2010 to 2019, each grid including XCO 2 and SIF, where the predicted ACE was 4% lower than ODIAC in 2019 for the Chinese region and indicated that larger predicting biases were mainly located around the big cities [28]. This GRNN model needs long-term series data that are difficult to collect when using multiple parameters, which could not further improve the prediction accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would extend the study areas, such as the American land area, to validate our proposed approach in the future. Another additional study built the grid-based prediction model by generalized regression neural network (GRNN) algorithm using a long time series of data from 2010 to 2019, each grid including XCO 2 and SIF, where the predicted ACE was 4% lower than ODIAC in 2019 for the Chinese region and indicated that larger predicting biases were mainly located around the big cities [28]. This GRNN model needs long-term series data that are difficult to collect when using multiple parameters, which could not further improve the prediction accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the values of emissions have a regional non-normal distribution, which affects the unbiased modeling and accurate estimation of ACEs. Several studies have attempted to reduce this effect using the sampling methods of training data (e.g., by segmenting the emission intensity into two parts and then constructing an estimation model on a segment basis [27,28]) and demonstrated better validation results for predicting anthropogenic CO 2 emissions at the national scale. However, these previous studies used few predictor variables and insufficiently evaluated the prediction results.…”
Section: Introductionmentioning
confidence: 99%
“…These estimates at the urban scale have widely been obtained by top-down inversion approaches (more details in supplementary note 1) based on atmospheric CO 2 measurements (e.g. Lauvaux et al 2020 for Indianapolis; Breon et al 2015 for Paris; Verhulst et al 2017 for Los Angeles; Mueller et al 2021 for Baltimore-Washington area; Basu et al 2020 for the United States), which allows independent evaluation and identification of potential quality issues of GHG inventories (Zhang et al 2022). Its applications in the estimation of anthropogenic GHG were reported by Manning et al (2011), Lauvaux et al (2020), andNASEM (2022).…”
Section: Introductionmentioning
confidence: 99%